The role of biogeochemical barriers in protecting aquatic ecosystems against pollution in agricultural environment - Łaskawiec, Edyta (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2015)
This review discusses the importance of ecotones with high plant diversity which are highly effective in retaining pollutants and waste. Biogeochemical barriers play a vital role in eliminating biogenic pollutants, pesticides and heavy metals. Belts of rush plants and meadow vegetation considerably expand the accumulation capacity of water bodies and watercourses. The mechanisms responsible for the protective role of biogeochemical barriers involve various processes such as sorption, sedimentation, denitrification and assimilation, which require the coexistence of plants and microorganisms in aquatic ecosystems. Buffer barriers were presented as one of the ecohydrology tools in agricultural landscapes.